Investigation of the performance and life cycle assessment of alkali-activated sintered sludge-slag-based permeable concrete - Ning, Xiangbo; Zhang, Jiayang; Zhuang, Can; Su, Qunyong; Zhong, Shunjie (Frontiers in Materials, 2024)
As urbanization continues to accelerate, the application of permeable concrete is becoming an increasingly prevalent practice. Nevertheless, the carbon dioxide emission issue associated with traditional permeable concrete cannot be overlooked. In this study, alkali-activated sintered sludge and slag were employed as raw materials to prepare alkali-activated sintered sludge-slag-based permeable concrete. The effects of sludge calcination temperature, sludge content, and binder-to-aggregate ratio on the compressive strength, porosity, and permeability coefficient of the permeable concrete were investigated through the implementation of one-way experiments. The formation mechanism of permeable concrete materials was analyzed using scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS), and a carbon emission assessment was performed. The findings indicated that an increase in sludge content resulted in a notable decline in the 28-day compressive strength, accompanied by a reduction in the Ca/Si ratio of the C-A-S-H hydration products, from 1.08 to 0.35. Conversely, the carbon emission assessment demonstrated that abiotic losses declined markedly with an increase in sludge content, effectively mitigating the carbon emission burden associated with construction materials.